Estimation of power generation from municipal solid wastes: A case Study of Ilorin metropolis, Nigeria - R. A. Ibikunle; I. F. Titiladunayo; B. O. Akinnuli; S. O. Dahunsi; T. M. A. Olayanju (Energy Reports, 2019)
In this study, attempt was made to estimate the quantity of municipal solid waste (MSW) generated per annum, the generation rate in kg/capita/day as well as the quantity and the fractions of the waste streams available for energy production. The physical characterization of the waste streams into fractions was conducted. The proximate and ultimate analyses of the waste fractions were performed. Heating values of the waste streams was determined experimentally using a bomb calorimeter. It was concluded that 1% increase in carbon and sulphur will increase heating value by 79.08% and 10.83% respectively while 1% increase in hydrogen and nitrogen decrease heating value by 30.2% and 619.1% respectively. The energy potential (EPMSW) of the MSW based on the energy content of 584 tons/day MSW, is about 3,244,444 kWh or 3,244 MWh, Electrical Power (EPPMSW) of about 40555 kW or 41 MW and Power to Grid of 27 MW.
Keywords: 330; Characterization; Energy potential; Generation rate; Heating value; Municipal solid waste; Power potential